Transition‐Metal‐Free Heterobiaryl Synthesis via Aryne Coupling. Issue 31 (22nd March 2019) - Saied, Tarak; Demangeat, Catherine; Panossian, Armen; Leroux, Frédéric R.; Fort, Yves; Comoy, Corinne
Abstract : We disclose, for the first time, an efficient route for the construction of various heterobiaryl backbones in fair to excellent yields using the Aryne coupling methodology. This study outlined the remarkable effect of external chelating ligands and salt additives on the heterocyclic partner reactivity in the aryne coupling reaction. Abstract : For the first time, an efficient route for the construction of various heterobiaryl backbones in fair to excellent yields using the aryne coupling methodology is disclosed. This study outlined the remarkable effect of external chelating ligands and salt additives on the heterocyclic partner reactivity in this coupling reaction.